Answer:
3/20 I think
Step-by-step explanation:
Answer:
1 one
Step-by-step explanation: just know
The distance formula is based on the Pythagorean Theorem:
Distance = Square Root [(X2 - X1)^2<span> + (Y2 - Y1)^</span>2<span>]
</span>Distance = Square Root [(7 -1)^2 + (-7 -1)^2]
Distance = Square Root [ 6^2 + -8^2]Distance = Square Root [ 36 + 64 ]Distance = Square Root [100 ]Distance = 10
Source:http://www.1728.org/distance.htm
The answer is d dtunbfdrtuikngfetuungdruijgrresssaaaaaweerttyuuiioopllmnvcxsawr